Augmented Reality Approach for Marker-based Human Posture Measurement on Smartphones - Basiratzadeh, Shahin (Université d'Ottawa / University of Ottawa, 2019)
Quantifying human posture and range of motion remains challenging due to the need for specific technologies, time for data collection and analysis, and space requirements. The demand for affordable and accessible human body position measurement requires alternative methods that cost less, are portable, and provide similar accuracy to expensive multi-camera systems. This thesis developed and evaluated a novel augmented reality mobile app for human posture measurement to bring marker-based body segment measurement to the point of patient contact. The augmented reality app provides live video of the person being measured, AprilTag2 fiducial markers locations in the video, processes marker data, and calculates angles and distances between markers. Results demonstrated that the mobile app can identify, track, and measure angles and distances between AprilTag2 markers attached to a human body in real-time with millimetre accuracy, thereby allowing researchers and clinicians to quantify posture measurements anywhere, at anytime.
Keywords: Augmented reality; Range of motion; Mobile application; Posture; Fiducial markers; Healthcare; Smartphone; Apriltag2; Measurement; Markers